Second-generation Tyrosine Kinase Inhibitors Nilotinib- and Dasatinib-induced Keratosis Pilaris: A Case Report and Review of the Literature - Hussein M. Alshamrani; Marwan Alsaedi; Hosam Alaradati (Wolters Kluwer Medknow Publications, 2024)
Tyrosine kinase inhibitors (TKIs) can cause cutaneous adverse reactions, with most manifestations resembling keratosis pilaris (KP). Eleven reports describe the onset of KP, with or without confirmation through skin biopsy, during treatment with second-generation TKIs. Herein, we review the current literature and report a clinical case of a 41-year-old male with chronic myeloid leukemia who developed KP-like eruptions during treatment with dasatinib and later nilotinib that cleared after discontinuation of the treatment. However, after switching to nilotinib, severe pruritus and follicular papules reappeared and necessitated dermatology consultation. A skin biopsy confirmed KP's diagnosis and switching the treatment to ponatinib resulted in the resolution of skin rash without pruritus. Alternative TKIs can help address intolerable cutaneous adverse reactions.